2014
DOI: 10.1097/wnr.0000000000000255
|View full text |Cite
|
Sign up to set email alerts
|

Brain mechanisms of social comparison and their influence on the reward system

Abstract: Whenever we interact with others, we judge them and whenever we make such judgments, we compare them with ourselves, other people, or internalized standards. Countless social psychological experiments have shown that comparative thinking plays a ubiquitous role in person perception and social cognition as a whole. The topic of social comparison has recently aroused the interest of social neuroscientists, who have begun to investigate its neural underpinnings. The present article provides an overview of these n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 91 publications
(103 reference statements)
1
25
0
2
Order By: Relevance
“…Here, greater "not me" ratings when viewing same sex bodies compared with opposite sex bodies was significantly associated with activation in regions involved in (illusory) own body perception and comparative processes (Kedia, Mussweiler, & Linden, 2014). To investigate this, we directly contrasted rating "not me" of same sex versus rating "not me" of opposite sex bodies.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Here, greater "not me" ratings when viewing same sex bodies compared with opposite sex bodies was significantly associated with activation in regions involved in (illusory) own body perception and comparative processes (Kedia, Mussweiler, & Linden, 2014). To investigate this, we directly contrasted rating "not me" of same sex versus rating "not me" of opposite sex bodies.…”
Section: Discussionmentioning
confidence: 80%
“…To investigate this, we directly contrasted rating "not me" of same sex versus rating "not me" of opposite sex bodies. Here, greater "not me" ratings when viewing same sex bodies compared with opposite sex bodies was significantly associated with activation in regions involved in (illusory) own body perception and comparative processes (Kedia, Mussweiler, & Linden, 2014). Yet, the same "not me" ratings but when viewing opposite sex bodies compared with same sex others did engage (body) perceptual and evaluative regions (Kedia et al, 2014).…”
Section: Discussionmentioning
confidence: 80%
“…This may suggest that the ACC is a common active region associated with social interactions. The dorsal ACC also plays a key role in the processing of prediction errors and expectation violation (Kedia et al, 2014;van der Molen et al, 2017), which may corroborate the common currency hypothesis since individuals viewing others as beneficial may reflect a "worse than T A B L E 3 Significant regions of activation for monetary comparisons split across upward and downward directions and significant regions of activation for social status comparisons split across upward and downward directions (Simmons et al, 2011;Späti et al, 2014), and selfinitiated actions in social exclusion trials (Wang et al, 2019). Addi- be associated with social threat and being intimidated by higher ranking others.…”
Section: Common Activity For Downward and Upward Comparisonsmentioning
confidence: 99%
“…There has been growing interest in exploring the neurological underpinnings of social comparisons using functional magnetic resonance imaging (fMRI). For example, neurobiological reviews on social comparisons have suggested a possible role of the reward system and the frontal-parietal system (Chiao, 2010;Kedia, Mussweiler, & Linden, 2014). Convergent evidence from multiple neuroimaging studies on social hierarchy reveal a network of brain regions associated with social status (i.e., ventral striatum, regions of the prefrontal cortex, inferior parietal lobe, and portions of the occipital lobe; Chiao et al, 2008Chiao et al, , 2009Zink et al, 2008;Freeman, Rule, Adams Jr, & Ambady, 2009;Marsh, Blair, Jones, Soliman, & Blair, 2009;Bault, Joffily, Rustichini, & Coricelli, 2011; see Chiao, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we explored several other sources, including (1) direct searches on the names of frequently occurring authors, (2) the bibliography and citation indices of the pre-selected articles, and (3) the reference r Luo et al r r 442 r list of related reviews [Aoki et al, 2015;Du and Chang, 2015;Falk et al, 2012;Fehr and Camerer, 2007;Insel and Fernald, 2004;Izuma, 2013;Jankowski and Takahashi, 2014;Kedia et al, 2014b;Rilling and Sanfey, 2011;Ruff and Fehr, 2014;Swencionis and Fiske, 2014;Tricomi and Sullivan-Toole, 2015]. The search resulted into 119 potential studies, which were further assessed according to the following criteria: (i) subjects were free from psychiatric or neurological diagnoses and neuropharmacological influence; (ii) subjects performed tasks in the context of social comparison; (iii) fMRI was used as the imaging modality; (iv) whole-brain generallinear-model-based analyses (rather than region of interest [ROI] analyses) were applied; (v) statistical models for contrasts of downward/upward social comparison or relevant parametric analyses were reported; and (vi) activations were presented in a standardized stereotaxic space (Talairach or MNI).…”
Section: Literature Search and Selectionmentioning
confidence: 99%